ANALISIS PERJANJIAN PENGADAN BARANG/JASA KONTRAK NOMOR : 03/KONTRAK/ PDAM/PMPK/VII/2013 OLEH PERUSAHAAN DAERAH AIR MINUM TIRTA SIAK KOTA PEKANBARU DENGAN CV. PUTRI CAHAYA RIAU - Tasya Anindita; Firdaus '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The procurement of goods/services the government is supporting the development, we need to hold an agreement. Agreement is an event where a promise to one another or in which two people were each promised to implement something. In the implementation of the agreement came two possibilities, namely, first performed as the contracted agreement, both agreements were not carried out as agreed, or have event of default. Facts show often found the process of procurement of goods / services are not in accordance with the agreement. What happens is that one party does not carry out his achievements. Examples Between PDAM Tirta Siak Pekanbaru with CV. Putri Cahaya Riau. With contracts made is a package of procurement and installation work check valve, gate valve and the water meter intake. Under the agreement the procurement of goods / services contracts No : 03/KONTRAK/PDAM/ PMPK/VII/2013 on July 29, 2013. Issues that will be examined in this study are: First, How Rights and Obligations between PDAM Tirta Siak Pekanbaru with CV. Putri Cahaya Riau according to contract No : 03/KONTRAK/PDAM/ PMPK/VII/2013? Secondly, How is the implementation of the agreement procurement of goods / services between PDAM Tirta Siak Pekanbaru with CV. Putri Cahaya Riau causing a breach of contract? Third, How settlement of defaults in the agreement procurement of goods / services between PDAM Tirta Siak Pekanbaru with CV. Putri Cahaya Riau? This type of research is a sociological law research. Source of data used are primary data and secondary data, data collection techniques using interview, and literature study. In this study the authors used a qualitative analysis, in drawing conclusions using inductive method of thinking. Results from this study were first, the rights and obligations of the foothold are the rights and obligations contained in the Contract No : 03/KONTRAK/PDAM/ PMPK/VII/2013. Second, in the event of default implementation is done by the CV. Putri Cahaya Riau, with no work at all. Third, the settlement is done only ask for compensation for Down Payment to the insurance company. Suggestions of authors First, the parties must implement the rights and obligations under the agreement, Second, the government should be more selective in choosing a partner procurement of goods / services, so as to minimize defaults. Third, the government should bring the case to the path of litigation. Because of the loss not only of Down Payment. But not the completion of the job.Keywords: Treaty-Default-Goods / Services